Geossistema, território e paisagem : o caso da Reserva Biológica de Sooretama - Lopes, Luana Gaspar do Nascimento (2011)
The main purpose of this dissertation is to investigate, through an integrated study of the landscape of relationships supported in the interface between society and nature, the case study of the Biological Reserve of Sooretama, located in the city of Sooretama, Espírito Santo – Brazil. Under this integrated approach it was possible to analyse the evolution of the landscape and the use and occupation of the land surrounding the Rebio through perception and valuation of the local residents, proposing a theoretical and methodological framework developed by Georges Claude and Bertrand, GTP model – geosystems, Planning and Landscape – (1997). This was a proposal for a hybrid model of analysis that integrates natural and social analysis of the landscape, breaking with the idea of a dichotomous geographic approach. The study consisted of collecting 140 stories from different communities around the protected area that allowed us to have an outline of the perception and awareness of these communities in the context of the regional landscape, focusing on different readings of the geographic space using the GTP method.